The Role of the Social Marketing Mix in Voluntary Counseling and Testing (VCT) Utilization among Pregnant Women in Banyumas Regency: A Qualitative Study - Arif Kurniawan; Arrum Firda Ayu Maqfiroch; Dian Anandari; Elviera Gamelia (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Background: The utilization of Voluntary Counseling and Testing (VCT) services by pregnant women, particularly antenatal checkups with HIV/AIDS testing, remains low in community health centers (in Indonesian: Puskesmas) in Banyumas Regency. Community health centers in Banyumas Regency have implemented a marketing mix for VCT services, but it is not yet optimal. This study aimed to examine the marketing mix, consisting of promotion, product, price, and location, regarding the utilization of VCT services in Banyumas Regency. Method: This qualitative research employed a phenomenological approach and was conducted in 2018. Data were collected through in-depth interviews and documentation studies. Participants included VCT counselor midwives, pregnant women who used VCT, and heads of community health centers with VCT clinics. Informants were selected based on predefined inclusion criteria to capture diverse perspectives. Six pregnant women served as supporting informants. The validity of the research was checked using source triangulation including core informants and supporting informants. Data were analyzed using manual content analysis, including data preparation, repeated reading, initial coding, code categorization, theme development, interpretation, and presentation of findings. Results: Community health centers in Banyumas Regency had implemented all four elements of the social marketing mix in promoting VCT services. However, VCT utilization, particularly among pregnant women, remained below expected levels. Among the four elements, promotion, specifically marketing communication activities aimed at informing and persuading the target population, was identified as the least effective component. Conclusion: This study highlights promotion as the key social marketing element requiring further development to improve the utilization of VCT among pregnant women. Strengthening promotional strategies through the use of audio-visual media may enhance awareness and encourage greater uptake of VCT services in antenatal care settings.